An Analysis of Lexical Collocation in King Charles’ Speech - Siti Rachmi; Abdul Hakim Yassi; Sukmawaty (Hasanuddin University, 2023)
Collocation is quite common to every native speaker. English language is restricted to collocation. It has set its own patterns that occur in natural way. Collocation takes in the form of lexical combination and grammatical combination. Respecting to King Charles III, he starts to deliver speeches on numerous occasion after becoming new monarch. The usage of collocation might differ widely from deeper meaning and context behind. This qualitative research is designed to analyze lexical collocation that exists in King Charles’ speech. The document obtained from speech text was published by website ‘PBS News Hour’. The research results points out that 15 collocation data were produced by King Charles III in his speech. It clearly reflects how he conveyed some collocation form to exact meaning. Those were accepted in its language system, culture, and real life. This research is expected to bring out the best in foreign students’ language proficiency, understanding other language system and culture differences.